Foundations of Religious Education in Kyrgyzstan and Models of Religious Education Worldwide - Jumabaev, Maksatbek (Scientific Journal of Faculty of Theology, 2022)
This article will discuss the debates surrounding the newly introduced religious education, specifically the "History of Religious Culture" course, in middle schools in Kyrgyzstan and evaluate different perspectives on this matter. This article aims to investigate the educational models employed worldwide for the teaching of religious studies, examine the foundations of religious education, and explore the extent of compatibility between the current practices of religious instruction and these models.